SOME PROBLEMS OF STANDARDS AND USE OFICT COMPETENCIES, TEACHERS,ADMINISTRATORS IN DISTANCE LEARNING - Bohachkov, Ю.М.; Kryvonos, O.M. (Journal of Information Technologies in Education (ITE), 2010)
Defines the problems that existing approaches to the definition of competence does not allow identifying the level of operational competence. Level of competence is expressed through the demonstration of activity. Moreover, components such as motivation, ethics, sociality and behavior can be expressed in terms ofexternal, internal and real performance indicators and criteria. A cognitive and opreatsional components are represented by classical knowledge and skills.